Theoretical and acmeological bases of professional self-actualization of the future teacher of pop singing - Zarytska, Аnna A.; Zarytskiy, Andrii (My University, 2018)
New orienting points of the preparation of the professionals in the sphere of educational and art field as well as transition from encyclopedical to acmeological and competence paradigm of the realization of the sense of the pedagogical profession determine discovery of the essence and structure of such a new formation as capacity for self-actualization which serves as a personal indicator of the readiness of the students to teach younger generations national and universal human values as well as develop their artistic potential, esthetic outlook and form bases of the life competence by means of the music art. In the context of the various approaches to understanding of the essence of the professional self-actualization in the modern science there is no unanimous definition of this term. However, most of the investigations point out to the importance of the actualization of the activity, development of the capacity to reveal and realize own potential, enrich axiological space of the own life and universe of other people. It is necessary to note that the problem of professional self-actualization is of complex interdisciplinary nature and one of the basic categories reflecting the process of personality becoming in philosophy, psychology, pedagogy and acmeology. This problem is particularly urgent for the teachers for whom capacity to self-development, self-actualization and self-realization is an indicator of the professionalism, mastership and readiness for the competent activity based on the democracy and humanism as well as enrichment of the pedagogical activity accompanied filled with personal meanings.
Keywords: Acmeological bases; Professional self-actualization; Future teacher; Pop singing